2011
DOI: 10.1016/j.foodchem.2010.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid oxidation in horse mackerel patties covered with borage-containing film during frozen storage

Abstract: a b s t r a c tLipid oxidation of horse mackerel (Trachurus trachurus) patties covered with fish gelatin-based films containing a borage seed extract were evaluated, including commonly used analytical indexes (peroxide value, thiobarbituric acid reactive substances, polyene ratio), as well as determination of volatile compounds, quantitation of oxidized triacylglycerols and analysis by Fourier transform infrared (FTIR) spectroscopy, during 240 days of frozen storage and subsequent thawing and 4 days-chilling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 53 publications
3
26
1
1
Order By: Relevance
“…Crude lipids extracted from horse catfish were also characterized by FTIR (Figure 1). Generally, the FTIR spectrum exhibited similar regions of functional groups vibrations as reported previously for mackerel fish lipids [42], farmed salmon fillets lipids [43], as well as for some vegetable oils [44].…”
Section: Analytical Evaluation Of Changes Occurring In Catfish Oils Dsupporting
confidence: 83%
See 3 more Smart Citations
“…Crude lipids extracted from horse catfish were also characterized by FTIR (Figure 1). Generally, the FTIR spectrum exhibited similar regions of functional groups vibrations as reported previously for mackerel fish lipids [42], farmed salmon fillets lipids [43], as well as for some vegetable oils [44].…”
Section: Analytical Evaluation Of Changes Occurring In Catfish Oils Dsupporting
confidence: 83%
“…The bands appearing at 975 cm −1 are related to the vibration in the molecules analyzed double bonds trans. Guiménez et al [42] have found this peak at about 968 cm −1 in the study of oxidation of mackerel oil. In the Figure 1 above, this peak is not visible.…”
Section: Analytical Evaluation Of Changes Occurring In Catfish Oils Dmentioning
confidence: 86%
See 2 more Smart Citations
“…It has also been used for the analysis of edible oils [124], horse mackerel patties [125] and canned tomato juice [126], in combination with other analytical methods which lead to similar conclusions, and therefore providing marker bands to improve the understanding of chemical changes taking place during processing and storage.…”
Section: Infrared Spectroscopymentioning
confidence: 99%